Pelatihan Tata Kelola Keuangan Untuk Meningkatkan Kinerja Keuangan Bagi Pelaku Usaha Kampoeng Rajoet Binongjati - Dede Hertina; Yana Hendayana; Sakina Ichsani; John Henry Wijaya; Gita Genia Fatihat; R Susanto Hendianto (Universitas Teknokrat Indonesia, 2023)
Financial management through good financial literacy can improve financial performance and become an important aspect for the progress of the company. Financial management can be done through accounting. Accounting is a systematic process to produce financial information that can be used for decision making for its users. This Financial Governance Training is a Community Service activity conducted at Kampoeng Rajoet Binong Bandung. As long as UMKM in West Java Province still use money as a medium of exchange, accounting is needed by UMKM in West Java Province. Accounting will provide several benefits for UMKM in West Java Province, including: (1) UMKM in West Java can find out the company's financial performance, (2) UMKM in West Java can know, sort, and differentiate company assets and owner assets, (3) UMKM in West Java can find out the position of funds both sources and uses, (4) UMKM in West Java can make the right budget, (5) MSMEs in West Java can calculate taxes, and (6) UMKM in West Java can find out the flow of cash during a certain period.